Norfloxacin suppresses Leptospira-induced inflammation through inhibiting p65 and ERK phosphorylation and NLRP3 inflammasome activation. (January 2022) - Xie, Xufeng; Zhang, Wenlong; Chen, Xi; Wu, Dianjun; Cao, Yongguo
Abstract: Leptospirosis is a worldwide re-emerging zoonosis caused by pathogenic Leptospira . Inflammatory storms induced by Leptospira are the reason to induce immunoparalysis and organ failures. Antibiotics are still the current mainstream treatment for leptospirosis. In addition to their antibacterial action, the immunomodulatory function of antibiotics has been paid more and more attention. In this study, the role of norfloxacin on Leptospira -induced inflammation was investigated. Treatment with norfloxacin down-regulated Leptospira -induced IL-1β and TNF-α both in vivo and vitro models. Further study showed that norfloxacin inhibited Leptospira -induced phosphorylation of p65 and ERK. Norfloxacin also inhibited the Leptospira -induced NLRP3 inflammasome activation with the increased level of Na/K–ATPase Pump β1 subunit and decreased level of Kcnk6. These results indicated that norfloxacin suppressed Leptospira -induced inflammation through inhibiting p65 and ERK phosphorylation and NLRP3 inflammasome activation. Norfloxacin may be a potential candidate for suppressing inflammatory storms caused by Leptospira . Highlights: Nor suppresses Leptospira -induced inflammation. Nor inhibits the phosphorylation of p65 and ERK during Leptospira infection. Nor inhibits Leptospira -induced NLRP3 inflammasome activation. Nor up regulates the expression of Na/Kβ1 subunit, down regulates the expression of Kcnk6 during Leptospira infection.